Гендерные сходства и различия в деятельности и оценках украинских предпринимателей - Исакова, Н. (Социология: теория, методы, маркетинг, 2001)
Gender similarities and differences in the activities and perceptions of the Ukrainian entrepreneurs are analysed. According to the data of sociological survey, the gender factor has a minor influence on business performance and success upon the background of the unfavorable external environment, including taxation burden, lack of financial resources, and constantly changing laws and regulations.